FUNGSI NOTARIS DALAM PEMBUATAN AKTA YANG DIBUBUHI DENGAN CAP JEMPOL SEBAGAI PENGGANTI TANDA TANGAN - Mas Wiranata, I Gede Ngurah; Novy Purwanto, I Wayan (Kertha Semaya : Journal Ilmu Hukum, 2015)
This Paper is the function of a notary public in an authentic deed spiked with thumbprint in lieu of a signature. Problems occurred that there are differences of opinion regarding the status of a judge in a court of law made by the notary deed with thumbprint in lieu of a signature when seen from the provisions of Article 44 paragraph (1) of Law Notary. This paper aims to understand and know about how to function in the notary deed authentic spiked with thumbprint in lieu of a signature. This paper, using the method of normative legal research with the type of analytical approach legislation. This paper presented a study that as Notary public official has the authority to approve the thumbprint affixed with the special power of attorney, this role is called Legalisation. The essence of the legalization of the deed under the hand is not to change the deed under the hand becomes an authentic deed, but rather with the fact that ratification of the parties or the penghadap can no longer deny what he had done, including affixing thumbprints in the deed, as a competent authority for it has witnessed and read the contents of the deed before the parties affix thumbprint.
Keywords: notary, deed, Thumbprint